MAGNETIC FIELD OF POLARIS - Usenko, I. A.; Bychkov, V. D.; Bychkova, L. V.; Plachinda, S. I. (Одеські астрономічні публікації, 2010)
25 effective magnetic field (Be) estimates of Polaris (α UMi) were obtained from July 1983 to December 2005 using 1m Zeiss and 6m BTA telescopes of SAO RAS, equipped by magnitometers. These data with added 7 ones from Borra et al. (1981), obtained in 1980 show that magnetizing force of Polaris vary from +162 to - 109 Gauss do not depend on the changes of pulsational amplitude, but Fourier analysis reveal variability of magnetic field with period of 3.97586 days, close well with its pulsational period of 3.96961 days.